Respuesta :
Answer:
z = 8
Step-by-step explanation:
Solve for z:
(z + 4)/3 - 6 = (2 (5 - z))/3
Put each term in (z + 4)/3 - 6 over the common denominator 3: (z + 4)/3 - 6 = (z + 4)/3 - 18/3:
(z + 4)/3 - 18/3 = (2 (5 - z))/3
(z + 4)/3 - 18/3 = ((z + 4) - 18)/3:
(z - 18 + 4)/3 = (2 (5 - z))/3
Add like terms. 4 - 18 = -14:
(z - 14)/3 = (2 (5 - z))/3
Multiply both sides by 3:
(3 (z - 14))/3 = (3×2 (5 - z))/3
(3 (z - 14))/3 = 3/3×(z - 14) = z - 14:
z - 14 = (3×2 (5 - z))/3
(3×2 (5 - z))/3 = 3/3×2 (5 - z) = 2 (5 - z):
z - 14 = 2 (5 - z)
Expand out terms of the right hand side:
z - 14 = 10 - 2 z
Add 2 z to both sides:
2 z + z - 14 = (2 z - 2 z) + 10
2 z - 2 z = 0:
2 z + z - 14 = 10
z + 2 z = 3 z:
3 z - 14 = 10
Add 14 to both sides:
3 z + (14 - 14) = 14 + 10
14 - 14 = 0:
3 z = 10 + 14
10 + 14 = 24:
3 z = 24
Divide both sides of 3 z = 24 by 3:
(3 z)/3 = 24/3
3/3 = 1:
z = 24/3
The gcd of 24 and 3 is 3, so 24/3 = (3×8)/(3×1) = 3/3×8 = 8:
Answer: z = 8
[tex]\dfrac{1}{3}(z+4)-6=\dfrac{2}{3}(5-z)\qquad\text{multiply both sides by 3}\\\\\not3^1\cdot\dfrac{1}{\not3_1}(z+4)-3\cdot6=\not3^1\cdot\dfrac{2}{\not3_1}(5-z)\\\\1(z+4)-18=2(5-z)\qquad\text{use distributive property}\\\\z+4-18=(2)(5)-(2)(z)\\\\z-14=10-2z\qquad\text{add 14 to both sides}\\\\z=24-2z\qquad\text{add 2z to both sides}\\\\3z=24\qquad\text{divide both sides by 3}\\\\\boxed{z=8}[/tex]